Observational study on immune response to yellow fever and measles vaccines in 9 to 15-month old children. Is it necessary to wait 4 weeks between two live attenuated vaccines?. Issue 20 (11th May 2015) - Michel, R.; Berger, F.; Ravelonarivo, J.; Dussart, P.; Dia, M.; Nacher, M.; Rogier, S.; Moua, D.; Sarr, F.D.; Diop, O.M.; Sall, A.A.; Baril, L.
Abstract Background The use of 2 live attenuated vaccines (LAV) is recommended to be simultaneous or after an interval of at least four weeks between injections. The primary objective of this study was to compare the humoral response to yellow fever (YF) and measles vaccines among children vaccinated against these two diseases, either simultaneously or separated by an interval of 7–28 days. Subjects and methods A prospective, multicenter observational study was conducted among children aged 9–15 months. The primary endpoint was the occurrence of positive yellow fever antibodies after YF vaccine by estimating the titers of neutralizing antibodies from venous blood samples. Children vaccinated against YF 7–28 days after receiving the vaccine against measles (test group) were compared with children vaccinated the same day against these two diseases (referent group). Results Analysis was performed on 284 children. Of them, fifty-four belonged to the test group. Measles serology was positive in 91.7% of children. Neutralizing antibodies against YF were detected in 90.7% of the test group and 92.9 of the referent group (p =0.6). In addition, quantitative analysis of the immune response did not show a lower response to YF vaccination when it took place 1–28 days after measles vaccination. Discussion In 1965, Petralli showed a lower response to the smallpox vaccine when injected 4–20 days after measles vaccination. Since then, recommendations are to observe an interval of four weeks between LAV not injected on the same day. Other published studies failed to show a significant difference in the immune response to a LAV injected 1–28 days after another LAV. These results suggest that the usual recommendations for immunization with two LAV may not be correct. Conclusion In low income countries, the current policy should be re-evaluated. This re-evaluation should also be applied to travelers to yellow fever endemic countries.